The Influence of Organizational Culture on Employee Performance Through Job Satisfaction and Work Motivation as Intervening Variables - Syamsiana, Syamsiana; Prasetya, Arik; Nurtjahjono, Gunawan Eko (International Journal of Artificial Intelligence Research, 2023)
Low job satisfaction, work motivation and bad organizational culture will lead to decreased employee performance. This study aims to determine the determinants of decreased employee performance at BUMN PT. PLN Persero, Sulselrabar Region. The population of respondents in this study were employees of PT. PLN Persero for the Sulselrabar Region works in the fields of planning, trade and services, transmission and transportation distribution, generator sector, finance sector, HR sector and general affairs. Data analysis used the Partial Least Square (PLS) approach with the help of the WarpPLS program. PLS is a Structural Equation Modeling (SEM) equation model based on components or variants. The results showed that organizational culture variables had a significant effect on job satisfaction, job satisfaction had a significant effect on work motivation, and work motivation had a significant effect on employee performance. At the same time organizational culture has no significant effect on employee performance, organizational culture has no significant effect on work motivation, job satisfaction has no significant effect on employee performance. The implications of this research can be used to improve employee performance at PT. PLN Persero Sulselrabar Region through organizational culture, job satisfaction, and work motivation.